Lavendula Angustifolia, Rosmarinus Officinalis, Thymus Serpyllum and Origanum rotundifolium: Exploring natural solutions for inflammation and blood sugar management - Vasiliki Lagouri; Sara Oumenoune Tebbi; Armando Caseiro; Maria Trapali (European Scientific Journal, ESJ, 2024)
The Lamiaceae family, including common herbs like rosemary and mint, is being investigated for its potential health benefits. In addition to numerous health benefits, research is looking into these plants' anti-inflammatory qualities and potential impacts on blood sugar regulation. More specifically, the Greek endemic Lamiaceae plants are proven to be of great importance, regarding their bioactive compounds and the antioxidant, antidiabetic, and anti-inflammatory properties they have. Researchers are interested in understanding how Lamiaceae plant compounds might work in the body. Besides, Antioxidants have an increasingly important function in reducing tissue damage and cytotoxicity caused by hydrogen peroxide and oxygen radicals in a variety of human disorders. This knowledge could lead to the development of natural approaches for managing inflammation and potentially even diabetes. These plant-based options may offer a milder alternative to some conventional medications. By supporting the body's natural regulatory systems, Lamiaceae plants could contribute to a more holistic approach to well-being. This study's objective was to review the literature on the anti-inflammatory, antidiabetic, and antioxidant properties of the Lamiaceae species Lavendula Angustifolia, Rosmarinus Officinalis, Thymus Serpyllum, and Origanum rotundifolium